Preparation and characterization of pentaammineruthenium-(histidine-83)azurin: thermodynamics of intramolecular electron transfer from ruthenium to copper. - Margalit, R (1984)
The reaction between a5RuH2O2+ (a is NH3) and Pseudomonas aeruginosa azurin at pH 7, followed by oxidation, yields a5Ru(His-83)3+-azurin(Cu2+) as the major product. Spectroscopic measurements (UV-visible, CD, EPR, and resonance Raman) indicate that the native structure is maintained in the modified protein. The site of ruthenium binding (His-83) was identified by peptide mapping. The a5RuHis/Cu ratio in the modified protein, determined from the EPR spectrum, is 1:1, and the reduction potentials (vs. normal hydrogen electrode, pH 7.0, 25 degrees C) are blue copper (Cu2+/1+), 320 +/- 2 mV; a5Ru(His-83)3+/2+, 50 +/- 10 mV. From measurements of the reduction potentials at several temperatures in the 5-40 degrees C range, delta H degree for intramolecular Ru2+ ----Cu2+ electron transfer was estimated to be -12.4 kcal mol-1 (1 cal = 4.184 J). Analysis of kinetic data in light of the electron transfer exothermicity indicates that the reorganizational enthalpy of the blue copper site can be no larger than 7.1 kcal mol-1.